The effect of antiplatelet and anticoagulant therapies on clinical outcome of patients undergoing decompressive craniectomy: a systematic review - Angelini, Chiara; Zangrossi, Pietro; Mantovani, Giorgio; Cavallo, Michele Alessandro; De Bonis, Pasquale; Scerrati, Alba (Frontiers in Neurology, 2024)
Objective: This systematic review aims to investigate a potential correlation between the administration of antiplatelets (APs) or anticoagulants (ACs) and perioperative complications, with a particular focus on hemorrhagic events, in patients undergoing decompressive craniectomy (DC). Additionally, the secondary objective is to assess the neurological outcomes in patients undergoing DC while taking APs/ACs, comparing them to patients not on APs/ACs. Methods: The study utilized PubMed and Science Direct as primary online medical databases for the systematic review. Articles underwent screening based on title, abstract, and full-text review. Four studies meeting inclusion criteria were selected for comprehensive analysis.Results: Our findings suggest that the administration of APs/ACs in patients undergoing DC does not significantly impact functional outcomes. Notably, the occurrence of rebleeding within six months and other complications, including infections, appears to be less frequent in patients taking APs compared to those not taking APs/ACs. Conclusions: Literature-derived data on the association between APs/ACs and DC presented considerable heterogeneity and insufficient volume for robust statistical analysis. Consequently, a definitive conclusion regarding the influence of suspending or continuing these therapies on complications and clinical outcomes cannot be confidently reached at present. To address this, a large-scale prospective study is warranted to gather substantial and precise data, facilitating a nuanced understanding of how to balance the risks and benefits associated with antiplatelet and anticoagulant agents in the context of decompressive craniectomy.